TOTAL OF MICROBIAL CONTAMINATIONS IN RICE CHICKEN EGGS SAVE IN ROOM TEMPERATURE - Nurseptiani Jusuf; Agusriyanto Yusuf; Al Ilham Bin Salim (LPPM Universitas Bina Mandiri Gorontalo, 2021)
Eggs are a food that is needed by the body because of the very large nutritional content in them. The number of microbes in eggs will increase with the length of storage. The purpose of this study was to determine the total amount of microbial contamination in eggs stored at room temperature. This research is descriptive quantitative using laboratory experimental methods. Samples were taken by purposive sampling as many as 10 eggs kept at room temperature for 1 week and 2 weeks. Data is presented in tabular form and accompanied by narration. The results showed that 2 samples of chicken eggs that exceeded the maximum limit of microbial contamination set by SNI 3929: 2009, namely (1x105 CFU / ml), namely the TAR4 code sample for 1 week storage time of 2.